Necrotic Core-Mediated Immune Suppression in a Patient-Derived Glioblastoma-on-Chip Model - Bayona, Clara; Randelovic, Teodora; Aranda, Eduardo; Olaizola-Rodrigo, Claudia; Mozas, Pilar; Vázquez, Enrique; Sanz, Rebeca; Ochoa, Iñaki (Jornada de Jóvenes Investigadores del I3A, 2025)
Necrosis emerges as a key driver of immune suppression in glioblastoma. Using a patient-derived organ-on-chip model, we demonstrate that necrotic niches induce T cell exhaustion and macrophage polarization, reshaping the immune landscape. Our findings uncover necrosis as a potential target to improve immune responses and guide new immunotherapy strategies for glioblastoma.